Nutritional strategies in supporting immune checkpoint inhibitor, PI3K inhibitor, and tyrosine kinase inhibitor cancer therapies - Fuller-Shavel, Nina; Davies, Emma Jane; Peleg Hasson, Shira (Frontiers in Nutrition, 2025)
Nutritional status of patients undergoing cancer treatment has been associated with cancer therapy and survival outcomes across multiple therapy types. Targeted therapies, including immune checkpoint inhibitors (ICIs), phosphatidylinositol 3-kinase (PI3K) inhibitors and EGFR-tyrosine kinase inhibitors (TKIs), are both influenced by and themselves influence the patients’ nutritional and metabolic status. Precision nutrition approaches that address specific aspects of targeted therapies, from minimizing toxicities and treatment resistance to potential therapeutic synergies, offer an important avenue to optimize clinical outcomes for patients receiving targeted oncological treatments as a part of an overall precision integrative oncology approach. Optimizing ICI treatment may necessitate gastrointestinal microbiome modulation and managing systemic inflammation with a variety of dietary approaches under study, including the Mediterranean diet, increasing fiber and fermented food intake, fasting and fasting mimicking diet and the ketogenic diet. Supplementation approaches using live biotherapeutics alongside ICIs predominate over prebiotic, postbiotic and synbiotic studies, which require further attention and investment, alongside human research on mycotherapy and fucoidan-based combinations. Optimizing PI3K treatment tolerance requires close attention to monitoring and managing glycemic control through nutrition, lifestyle and pharmacological intervention as necessary, and in supporting patients with EGFR-TKIs both nutritional prehabilitation and close attention to managing gastrointestinal toxicities is paramount. Rational individualized approaches based on detailed and dynamic clinical assessment of patient-, cancer- and treatment-related factors, using validated prognostic scores and biomarkers, are needed to maximize the potential of precision nutrition now and in future trials in this arena.